The Communication Style of Influencers in Developing Adolescent Character on Social Media - Sukron Mazid; Atsani Wulansari; Siti Maizul Habibah; R. Yogie Prawira; Angela Carolina Flores Riquelme (The Journal of Society and Media, 2026)
Social media has become a primary space for adolescent identity construction, where influencers function as models of communication and behavior. Without adequate control and digital literacy, influencers’ communication styles may shape adolescents’ character in an uncritical and instantaneous manner, potentially introducing values that diverge from national character ideals. This study aims to analyze how influencers’ communication styles on social media affect adolescent character formation. A qualitative descriptive approach with a case study method was employed involving adolescents aged 13–18 years in Magelang City who actively use Instagram and TikTok. Data were collected through in-depth interviews, social media observations, and digital documentation. The data were analyzed using data reduction, data display, and verification techniques. Data validity was ensured through source triangulation and member checking. The findings reveal that persuasive, personal, and expressive communication styles used by influencers significantly influence adolescents’ attitudes, values, and character formation in both positive and negative ways. These findings highlight the importance of digital literacy in strengthening adolescent character in the information era. The study provides insights for educators, parents, and policymakers in designing effective digital mentoring strategies and offers a foundation for further research